Amidated pectin with amino acids: Preparation, characterization and potential application in Hydrocolloids. (August 2022) - Wang, Pengkai; Gao, Yifan; Wang, Daqing; Huang, Zhili; Fei, Peng
Abstract: The poor gelatability of pectin is a barrier to its application in hydrogel field. In this study, glutamic acid, glycine and lysine (representing acidic, neutral and basic amino acids respectively) were grafted onto the pectin (Na-Pe) molecules in an ice bath, and the grafting ratio of amidated pectin was 4.98% (glutamic acid grafted pectin, Glu-Pe), 6.35% (glycine grafted penctin, Gly-Pe) and 7.78% (lysine grafted penctin, Lys-Pe), respectively. It was explored the effects of the three amino acids on the gel properties of pectin and evaluated their potential applications in drug sustained-release. Fourier transform infrared spectrum, X-ray photoelectron spectrum and proton nuclear magnetic resonance analysis indicated that the amidogen of the amino acids was bonded to carboxy group of the Na-Pe. After grafting with the amino acids, the viscosity of the amidated pectin was significantly improved, which was improved from 36.7 (Na-Pe) to 62.5 (Glu-Pe), 186.4 (Gly-Pe) and 129.8 mPa s (Lys-Pe). In addition, the gel strength the pectin was significantly improved by the introduction of the amino acids. In the absence of sucrose, Gly-Pe and Lys-Pe could form a solid hydrogel, while the Na-Pe and Glu-Pe could not. Moreover, Glu-Pe and Gly-Pe showed good sustained release ability of matrine, which indicates that they have broad application potential in the field of sustained-release hydrogels. Graphical abstract: Image 1 Highlights: Amidated pectin was prepared at low temperature. The emulsifying properties of native pectin were improved after modification. In the absence of sucrose, the amidated pectin could form a solid hydrogel.